A new surgical treatment for abdominal wall defects: A vascularized ribs-pleural transfer technique that can be used with or without a thoracic umbilical flap a case report. Issue 9 (March 2018) - Chen, Qiang; Liu, Qi; Suo, Yan; Xie, Qingping
Abstract: Rationale: Abdominal wall defects are common after tumor resection. Patient concerns: We report an 83-year-old male patient with recurrent tumors in his abdomen, and who had an incision wound that could not be directly closed. Mesh was not suitable because the wound was infected. Diagnoses: Abdominal wall defect result from the resection of recurrent tumor. Interventions: We carried out a vascularized ribs-pleural transfer operation. Outcomes: After the surgery, the patient gained a functional recovery. No evidence of recurrence was noted 1 year after operation, and the patient showed no symptoms of abdominal compression syndrome. Lessons: We discuss the clinical diagnosis, treatment, and follow up and argue that the vascularized ribs-pleural transfer technique is a good method to deal with abdominal wall defects.